Плазмонні моно- та біметалічні наночастинки золота і срібла як перспективні засоби комплексної терапії онкозахворювань (за матеріалами наукового повідомлення на засіданні Президії НАН України 11 вересня 2019 р.) - Муха, Ю.П. (Вісник НАН України, 2019)
У представленому циклі робіт розроблено і відпрацьовано системний підхід
до одержання стабільних наночастинок золота, срібла та їх біметалічних
композицій у водному середовищі за присутності біосумісного компонента — незамінної амінокислоти триптофану. Продемонстровано, що склад
нанорозмірних частинок Ag/Au визначає як характеристики смуги локалізованого поверхневого плазмонного резонансу металу у спектрах поглинання, так і їх біологічну активність. Показано можливість спрямованого
синтезу наночастинок металів з контрольованими характеристиками з
використанням хімічного та фотохімічного методів. Встановлено експериментальні умови отримання магніто-плазмонних нанокомпозитів як
препаратів для комплексної терапії онкозахворювань. In the presented work, a systematic approach is developed to prepare stable colloids of noble metal nanoparticles (NPs)
as promising agents for cancer treatment. Mono- and bimetallic gold and silver NPs of alloy and core-shell type were
prepared in aqueous medium using biocompatible component tryptophan as metal reducer and particle stabilizer.
The impact of metal components/composition as well as metal topological distribution within NPs on optical properties
and biological activity is discussed. Only one localized surface plasmon resonance (LSPR) band is characteristic for
bimetallic NPs. In case of alloy Ag/Au nanoparticles the maximum is located between the maxima inherent to the LSPR
bands of individual metals and shifts from 411 nm (silver) to 526 nm (gold) with decreasing Ag:Au molar ratio. In case of
bimetallic core-shell NPs LSPR absorption band of previously formed monometallic particles, used as a core, disappears
during the synthesis while LSPR band of the second metal grows in the spectra of the same colloid. Among studied alloy
systems Ag/Au nanoparticles with metal ratio 3:1 had the maximal anticancer effect towards HCT116, 4T1, HUH7 cell
lines, while the toxicity was found significantly decreased in non-cancerous HEK293 cell lines. During antitumor activity
studies in vivo on mouse with Lewis lung carcinoma treated with alloy (Ag:Au = 3: 1, 1 : 1, 1 :3) and core-shell nanoparticles.
(Aucore/Agshell, Agcore/Aushell), the system with Ag core covered by Au shell appeared to be the most effective.
The synthesis of nanoparticles with controlled properties was demonstrated with the use of chemical and photochemical
methods. The activation of redox process between metal ions and tryptophan with UV irradiation at 280 nm,
corresponding to the position of the indole absorption band of amino acid, allows to affect the optical properties of the
system, characteristics of nanoparticles and their self-assembling in colloid depending on experimental parameters like
temperature of reaction, output optical power density and duration of irradiation.
Chemical and photochemical methods were applied for preparation of magneto-plasmonic nanostructures composed
of magnetic iron oxide core and gold/silver shell. The optical properties of magneto-plasmonicFe3O4/Au(Ag) nanocomposites,
namely position of plasmon resonance band maximum and absorbance in near infrared region, can be adjusted by
varying the temperature of reaction from 25 to 100 °C and applying UV irradiation. Such nanosystems possess properties
inherent to both individual components and can be applied in biomedical field for targeted drug delivery and therapy.